LEADERSHIP DEVELOPMENT TRAINING FOR BRAZILIAN ORTHOPEDIC SURGEONS - Oberlohr, Verena; Giordano, Vincenzo; Hungria, José Octavio Soares; Caiero, Marcelo; Pires, Robinson Esteves; Silva, Luiz Henrique Penteado da; Pallottino, Alexandre; Sanchez, Gustavo Tadeu; Labronici, Pedro José; MacKechnie, Madeline; Miclau, Theodore (Acta ortopedica brasileira, 2024)
ABSTRACT Objective: To report on the experience and impressions of the Brazilian orthopedic trauma surgeons attending the Leadership Development Program (LDP) hosted by the Sociedade Brasileira do Trauma Ortopédico (SBTO) in Sao Paulo, Brazil on November 4, 2022. Methods: Forty-eight orthopedic trauma surgeons from five different regions throughout Brazil were provided a link to complete The Big Five Test, a validated online personality assessment. The questionnaire was available in Portuguese and was intended to provide a background on individual personality traits and their influence on interpersonal interactions. The LDP integrated content from literature reviews specific to Latin America, established leadership programs from leading business schools, and various subject matter experts. Prior to the start of the LDP, participants received a pre-course survey evaluating demographic information, a needs assessment, and the prioritization of leadership topics utilizing a 5-point Likert-scale. Attendees participated in the one-day, interactive LDP focusing on the fundamental principles of leadership development, communication, personal development, emotional intelligence and negotiation. Following the LDP, a post-course evaluation was administered to determine the participants’ overall experience, and suggestions for LDP improvement. Results: Forty-one of the forty-eight course participants completed the pre-course evaluation, whereas forty-six of the forty-eight participants completed the post-course evaluations. Overwhelmingly, the lack of opportunity was most prevalently reported as the main obstacle to attending a leadership course, as cited by 56% of respondents. Conclusion: Expanding the accessibility, diversity, and customizability of leadership programs can facilitate the development of personal tools needed to move healthcare forward. Critical topics include emotional intelligence and other differentiating leadership qualities that distinguish true transformational and servant leaders. Advancing leadership skills can stimulate networking, expose learners to experiential learning styles, inspire others to create positive change, and engender creative solutions for systematic improvements and health outcomes. Level of Evidence III; Individual Case-Control Studies. RESUMO Objetivo: Relatar a experiência e as impressões de cirurgiões de trauma ortopédico brasileiros participantes do Programa de Desenvolvimento de Liderança (PDL), organizado pela Sociedade Brasileira do Trauma Ortopédico (SBTO), em São Paulo, Brasil, em 4 de novembro de 2022. Métodos: Quarenta e oito cirurgiões de trauma ortopédico de cinco regiões diferentes do Brasil receberam um link para preencher o The Big Five Test, uma avaliação de personalidade on-line validada. O questionário estava disponível em português e pretendia fornecer informações básicas sobre traços de personalidade individuais e sua influência nas interações interpessoais. O PDL integrou conteúdo de análises de literatura específicas da América Latina, e programas de liderança estabelecidos pelas principais escolas de negócios e por vários especialistas no assunto. Antes do início do PDL, os participantes receberam uma pesquisa pré-curso solicitando informações demográficas, uma avaliação de necessidades e a priorização de tópicos de liderança utilizando uma escala Likert de 5 pontos. Os participantes participaram do PDL interativo de um dia com foco nos princípios fundamentais de desenvolvimento de liderança, comunicação, desenvolvimento pessoal, inteligência emocional e negociação. Após o PDL, foi realizada uma avaliação pós-curso para determinar a experiência geral dos participantes e sugestões para melhoria do PDL. Resultados: Quarenta e um dos quarenta e oito participantes do curso concluíram a avaliação pré-curso, enquanto quarenta e seis dos quarenta e oito participantes concluíram a avaliação pós-curso. A falta de oportunidade foi relatada com maior prevalência como o principal obstáculo para frequentar um curso de liderança, conforme citado por 56% dos entrevistados. Conclusão: Expandir a acessibilidade, a diversidade e a personalização dos programas de liderança podem facilitar o desenvolvimento de ferramentas pessoais necessárias para fazer avançar os cuidados de saúde. Os tópicos críticos incluem inteligência emocional e outras qualidades de liderança diferenciadas, que distinguem verdadeiros líderes transformacionais e servidores O avanço das competências de liderança pode estimular o networking, expor os alunos a estilos de aprendizagem experiencial, inspirar outros a criar mudanças positivas e gerar soluções criativas para melhorias sistemáticas dos resultados na saúde. Nível de Evidência III; Estudos de caso-controle individuais.